1989
DOI: 10.1111/j.1526-4610.1989.hed2901042.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and Anti‐Phospholipid Antibodies

Abstract: Anti-phospholipid antibodies (APA), initially described with SLE, have in recent years received much attention because of an associated increased risk of thrombo-embolic disease, recurrent abortion and thrombocytopenia. Although commonly seen with SLE or other collagen vascular diseases, the antibodies frequently occur in the absence of any such disease. Neurologic complications include transient or permanent ischemic episodes, migraine or related phenomena, myelopathy and a Guillain-Barré type syndrome. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 11 publications
1
16
0
1
Order By: Relevance
“…In fact, it is possible that aPLs exert a role in only a subgroup of migraine patients that could be at high risk of ischemic stroke. This last concept seems to be strengthened by the high number of reported associations between migraine, aPLs and stroke [3,13,[15][16][17], In these studies, in compliance with our findings, a severe type of headache was detected in every aPLs-positive patient.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In fact, it is possible that aPLs exert a role in only a subgroup of migraine patients that could be at high risk of ischemic stroke. This last concept seems to be strengthened by the high number of reported associations between migraine, aPLs and stroke [3,13,[15][16][17], In these studies, in compliance with our findings, a severe type of headache was detected in every aPLs-positive patient.…”
Section: Discussionsupporting
confidence: 78%
“…In particular, the wide number of descriptions of association of LA and aCAs with migraine has suggested their possible pathogenetic implication in vascular headache [13,[15][16][17], However, such a hypothesis has not been supported by recent inves tigations performed on migrainous patients [18] and on patients with systemic lupus erythematosus [19,20] that failed to show any specific association between migraine and aPLs. These conflicting results could be explained by the hypothesis that the association between aPLs and migraine concerns only a particular group of patients.…”
Section: Introductionmentioning
confidence: 84%
“…In the case of carotid dissection, blood may partially flow through the residual lumen or through a false passage and, after lysis of the clot, a normal lumen is re-established. High aPL levels have also been found in neurological disease: migraine [14,23], Sneddon's Syndrome with livedo retieularis [15], multiinfarct dementia [9], isehemia optic neuropathy, chorea, transverse myelitis, GuiUan Barr~ syndrome and seizures. As previously reported [6], serial angiographic examinations may show that, when not reeanalized, arterial dissection may transform itself into an apparently total occlusion at the origin of the ICA, perfectly simulating a primary carotid thrombosis (as shown in one of our patients: (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…A follow up on these children for two years disproved a number of prior assumptions: the first, in one-third of the children, high levels of aCL were detected even though they had not received any anti-epileptic medication and the antibody level decreased as expected with age without relation to the dose of drugs or term of therapy; the second, the frequency of convulsions did not influence the level of aCL; the third, the cross-reaction between aCL and neurons was more likely than the thrombogenic activity involved in APS as MRI findings were normal. Since migraine seems to be more common in patients with SLE, some studies have investigated a possible association with aCL (Markus and Hopkinson, 1992), and studies in adults with migraines have suggested a significant relationship between aCL and migraines (Shuaib et al, 1989;Tietjen et al, 1998). Verrotti et al (2001) studied this relationship in children and adolescents and found no association.…”
Section: Discussionmentioning
confidence: 99%